Assessment of Nursing Care Activities for Patients with Acute Ischemic Stroke at Thanh Nhan Hospital in 2024 - Thi Nguyet, Nguyen; Tuyet Trinh, Nguyen; Thi Uyen, Doan; Trung Nguyen, Nguyen; Hong Thu, Be (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
Objective: This study aimed to evaluate the performance of nursing care activities for patients with acute ischemic stroke at Thanh Nhan Hospital in 2024. Methods: A prospective descriptive study was conducted on 140 eligible patients with acute ischemic stroke. Data were collected using a structured assessment tool based on stroke nursing care guidelines and medical records. Nursing activities were evaluated using a three-level scale: not performed, insufficiently performed, and well performed. Results: The overall proportion of well-performed nursing care activities was 83%. High performance was observed in monitoring vital signs, respiratory care, health education, and rehabilitation guidance. However, several activitiessuch as pressure ulcer prevention, regular nutritional assessment, and neurological monitoring during later hospitalization days were not consistently maintained. A general decrease in the frequency of care activities was noted over time. Conclusion: Nursing care quality for patients with acute ischemic stroke at Thanh Nhan Hospital was generally good, though improvements are needed in pressure ulcer prevention and periodic nutritional evaluation.